2016
DOI: 10.1080/19390211.2016.1237400
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Tea and Sour Tea (Hibiscus sabdariffaL.) Supplementation on Oxidative Stress and Muscle Damage in Athletes

Abstract: GTE and STE supplementation have beneficial effects on oxidative stress status in male athletes. However, both kinds of tea extract did not affect muscle damage status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 26 publications
3
64
0
1
Order By: Relevance
“…They also induce phase II in enzymes and antioxidants, such as glutathione and S-transferase [8]. Tea extracts, especially ethanol extracts, are components of supplements and nutritional additives [9], which also contain other ingredients, such as unsaturated fatty acids, mineral components and vitamins. Moreover, such products often contain active forms of thiamine, which is used to treat various ailments, e.g., mild vitamin B1 deficiencies [10,11], or when it is necessary to apply parenteral hyperalimentation [12].…”
Section: Introductionmentioning
confidence: 99%
“…They also induce phase II in enzymes and antioxidants, such as glutathione and S-transferase [8]. Tea extracts, especially ethanol extracts, are components of supplements and nutritional additives [9], which also contain other ingredients, such as unsaturated fatty acids, mineral components and vitamins. Moreover, such products often contain active forms of thiamine, which is used to treat various ailments, e.g., mild vitamin B1 deficiencies [10,11], or when it is necessary to apply parenteral hyperalimentation [12].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of tea is popularly consumed as a healthy beverage in many parts of the world (Kafeshani et al, ). Due to its high content of polyphenolic components, especially catechin, epicatechin gallate, epigallocatechin‐3‐gallate, and epigallocatechin, green tea is utilized as a folk medicine in the treatment of various metabolic disorders including obesity, hypertension, diabetes, and cardiovascular diseases (Bøhn, Ward, Hodgson, & Croft, ; Hadi et al, ). Clinical trials that tried to evaluate the precise effects of green tea supplementation regarding the NAFLD have provided paradoxical results, and its optimal role in the clinical management of this disease has not been fully established (Hussain, Habib Ur, & Akhtar, ; Pezeshki, Safi, Feizi, Askari, & Karami, ; Tabatabaee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings provided a summary for promising effect of sour tea on CVD metabolic risk factors. There was lack of adequate information from clinical studies on other CVD risk factors, which could be modulated by sour tea such as body weight (Chang et al, ) and oxidative stress (Hadi et al, ). Sour tea has bioactive compounds such as organic acids, anthocyanins, and flavonoids, which have been reported to be responsible for its antioxidant and anti‐inflammatory activities (Da‐Costa‐Rocha, Bonnlaender, Sievers, Pischel, & Heinrich, ; Formagio et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, sour tea was conventionally prescribed to control hypertension ((Serban et al, ). Moreover, recent studies have also shown that sour tea has beneficial effects on glucose status (Mozaffari‐Khosravi, Ahadi, & Tafti, ), oxidative stress (Hadi et al, ) and lipid profile (Mozaffari‐Khosravi, Jalali‐Khanabadi, Afkhami‐Ardekani, & Fatehi, ). The lipid‐lowering effects of sour tea have been investigated by various scholars.…”
Section: Introductionmentioning
confidence: 99%